Ranavirus Amplification in Low-Diversity Amphibian Communities - Bienentreu, Joe-Felix; Schock, Danna M.; Greer, Amy L.; Lesbarrères, David (Frontiers in Veterinary Science, 2022)
In an era where emerging infectious diseases are a serious threat to biodiversity, epidemiological patterns need to be identified, particularly the complex mechanisms driving the dynamics of multi-host pathogens in natural communities. Many amphibian species have faced unprecedented population declines associated with diseases. Yet, specific processes shaping host-pathogen relationships within and among communities for amphibian pathogens such as ranaviruses (RV) remain poorly understood. To address this gap, we conducted a comprehensive study of RV in low-diversity amphibian communities in north-western Canada to assess the effects of biotic factors (species identity, species richness, density) and abiotic factors (conductivity, pH) on the prevalence and severity of infection. Across two years and 18 sites, with communities of up to three hosts (wood frog, Rana sylvatica; boreal chorus frog, Pseudacris maculata; Canadian toad, Anaxyrus hemiophrys), we observed that RV prevalence nearly doubled with each additional species in a community, suggesting an amplification effect, in aquatic as well as terrestrial life-history stages. Infection intensity among infected wood frogs and boreal chorus frogs also significantly increased with an increase in species richness. Interestingly, we did not observe any effects of host density or abiotic factors, highlighting the importance of including host identity and species richness when investigating multi-host pathogens. Ultimately, only such a comprehensive approach can improve our understanding of complex and often highly context-dependent host-pathogen interactions.